2013
DOI: 10.1177/0954405413476495
|View full text |Cite
|
Sign up to set email alerts
|

Finite element study of stress and strain state during hot tube necking process

Abstract: Tube necking is a common process used for manufacturing pressure vessels, for example, compressed natural gas capsules, categorized under general spinning processes. An experimentally validated finite element model suited to the process is incorporated to study the deformation, and state of strain and stress in the contact zone. The in situ variation of stress and strain is illustrated via colored contour plots, and Cartesian and polar diagrams. It is shown that in some areas, there are similarities and differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…The bending due to compressive strain along the axial direction in Zone and the axial extension in Zone together ampli ed the positive strain. Such ndings are consistent with the deformation pattern of Zoghi and Fallahi Arezoodar [7] in their research on neck spinning. The excessive elongation of the outer metal at the rim in Zone was caused by the unconstrained material at the rim of the bottle mouth, which is consistent with the behavior mentioned by Hamed et al [17] in their research on tube spinning.…”
Section: The Plastic Strain Distribution Of Different Thickness Layerssupporting
confidence: 90%
See 2 more Smart Citations
“…The bending due to compressive strain along the axial direction in Zone and the axial extension in Zone together ampli ed the positive strain. Such ndings are consistent with the deformation pattern of Zoghi and Fallahi Arezoodar [7] in their research on neck spinning. The excessive elongation of the outer metal at the rim in Zone was caused by the unconstrained material at the rim of the bottle mouth, which is consistent with the behavior mentioned by Hamed et al [17] in their research on tube spinning.…”
Section: The Plastic Strain Distribution Of Different Thickness Layerssupporting
confidence: 90%
“…6. In manufacturing certain pressure vessels using the tube spinning process, Zoghi and Fallahi Arezoodar [7] , highlighted the existence of thickening, thinning, elongation, compression, bending, and shearing in the deformation zone during the neck spinning process of the bottle mouth. To further investigate the strain state of the bottle mouth, the plastic strain distribution on each thickness layer in Fig.…”
Section: The Plastic Strain Distribution Of Different Thickness Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al [7] had analyzed the different roller angles using upper bound method and simulations. Zoghi et al [8] had done finite element analysis of hot tube necking process for 42CrMo steel. Xia et al [9] had done the analysis of flow forming for non axisymmetrical geometry.…”
Section: Fig 2 Backward Flow Forming Configurationmentioning
confidence: 99%
“…Zoghi et al [2] did finite element analysis of hot tube necking process for 42CrMo steel. The working temperature was set as 850° C. The study was concentrated for plastic strain and von-mises stresses and they were found that the equivalent plastic strain value is lower at the inner surface compared to top and middle surface.…”
Section: Introductionmentioning
confidence: 99%